Treatment-Free Remission in Chronic Myeloid Leukemia and New Approaches by Targeting Leukemia Stem Cells - Chen, Yilin; Zou, Jing; Cheng, Fanjun; Li, Weiming (Frontiers in Oncology, 2021)
Treatment-free remission (TFR) after discontinuing TKI has increasingly become a new goal for CML treatment. However, TKI only “alleviates” CML, and relapse after discontinuation has become a key factor hindering patient access to attempt TFR. More emphasis should be placed on kinase-independent mechanisms and targeting quiescent, insensitive LSCs to achieve long-term survival in patients. In this study, we summarized recent advances in the fields of TKI discontinuation and new approaches targeting stem cells to improve treatment-free remission. In addition, we discussed advances in TKI dose reduction, relapse predictors, monitoring methods . We believe that this review will present comprehensive and latest advances in the fields of TKI discontinuation, TKI dose reduction, relapse predictors, monitoring methods, approaches targeting stem cells.